PERTANGGUNGJAWABAN PIDANA PELAKU PENYIMPANGAN SEKSUAL EKSIBISIONISME - Pandu Resky Deseto (2023)
Exhibitionism is a mental disorder that perpetrators have with their sexual fantasies characterized by a tendency to show genitals or genitals to the opposite sex. The research method used by the author is a normative juridical research method. The author in his research uses several kinds of problem approaches, among others, the statute approach and the case approach with the aim of knowing the perspective of Indonesian criminal law on the crime of sexual perversion exhibitionism. The author in his research also found some results, among others, that the perpetrator's responsibility is determined based on the examination conducted by experts to determine the provision of imprisonment to the perpetrator because the perpetrator who has sexual disorders can not guarantee will be able to return to being a person who does not repeat his actions, therefore rehabilitation is needed for perpetrators who have mental disorders. The author again draws the conclusion that the determination of the criminal liability of the perpetrator of the crime of exhibitionism is adjusted to the conditions that accompany the patient in a particular legal case, which has been examined by psychologists and psychiatrists.